Bathymetry of reservoirs using altimetric data associated to optical images. Issue 11 (1st June 2022) - Bacalhau, José Ráurium; Ribeiro Neto, Alfredo; Crétaux, Jean-François; Bergé-Nguyen, Muriel; Moreira, Daniel Medeiros
Highlights: Terrain profiles surveyed by the ICESat-2 represented properly the topography of the reservoir. The combination of altimetric data and optical images generated contours with acceptable accuracy. The elevation-area-volume curves had satisfactory values of correlation and RMSE. Abstract: The semiarid region of Brazil is highly dependent on reservoirs, and precise bathymetric data are essential for understanding the dynamics and storage variability of these water bodies. This study aimed to develop the application of bathymetric calculation using the observed water level and ICESat-2 satellite terrain profile data of large and medium-sized reservoirs. The combination of satellite images with altimetric data allows for the extraction of water contours, whose points contain elevation information. A digital terrain model (DTM) was generated, and an elevation-area-volume (EAV) curve was calculated for two reservoirs in Northeast Brazil, Sobradinho and Poço da Cruz, which have capacities of 34.116 and 0.4837 km 3, respectively. The water level from ICESat-2 was compared to that of the observed data from the Sobradinho, and DTM and EAV curves were analyzed for the two reservoirs. Using the water level from Sobradinho reservoir stations, this method covered 99% of the useful volume. The ICESat-2 data covered 50% of the storage capacity in the Sobradinho and 89% in Poço da Cruz. The in-situ and ICESat-2 data-based EAV curves showed volumes with Pearson's correlations equal to 0.99 for both reservoirs, and normalized root mean square errors of 2.62% and 4.13% for Sobradinho and Poço da Cruz, respectively. The results revealed that this strategy can be economic and viable, as it uses available free data with the potential to generate high-resolution bathymetry in reservoirs with different geometric characteristics.